Knowledge Sharing Intention terhadap Innovative Work Behaviour Karyawan di PT. XYZ (nama disamarkan) - Winata, Janet Hadisurya; Gunawan, Agus; Kornarius, Yoke Pribadi; Caroline, Angela (Jurnal Ilmiah Wahana Pendidikan, 2024)
The study aims to determine the influence of Knowledge Sharing Intention variable on Innovative Work Behaviour in employees at PT. XYZ. The results show that the influence of Knowledge Sharing Intention variable on Innovative Work Behaviour variable is 63.5%. From the frequency distribution results in the table, it can be seen that employees at PT. XYZ tend to have good Knowledge Sharing Intention and Innovative Work Behaviour. However, for the level of innovativeness, superiors tend to be more innovative than subordinates who do not have subordinates. Therefore, to increase the level of innovation of employees, superiors must provide means for subordinates to be more innovative, because superiors influence the level of innovation of their employees